Vertical variation in leaf functional traits of Parashorea chinensis with different canopy layers - Jin, Nan; Yu, Xiaocheng; Dong, Jinlong; Duan, Mengcheng; Mo, Yuxuan; Feng, Leiyun; Bai, Rong; Zhao, Jianli; Song, Jia; Dossa, Gbadamassi Gouvide Olawole; Lu, Huazheng (Frontiers in Plant Science, 2024)
Canopy species need to shift their ecological adaptation to improve light and water resources utilization, and the study of intraspecific variations in plant leaf functional traits based at individual scale is of great significance for evaluating plant adaptability to climate change. In this study, we evaluate how leaf functional traits of giant trees relate to spatial niche specialization along a vertical gradient. We sampled the tropical flagship species of Parashorea chinensis around 60 meters tall and divided their crowns into three vertical layers. Fourteen key leaf functional traits including leaf morphology, photosynthetic, hydraulic and chemical physiology were measured at each canopy layer to investigate the intraspecific variation of leaf traits and the interrelationships between different functional traits. Additionally, due to the potential impact of different measurement methods (in-situ and ex-situ branch) on photosynthetic physiological parameters, we also compared the effects of these two gas exchange measurements. In-situ measurements revealed that most leaf functional traits of individual-to-individual P. chinensis varied significantly at different canopy heights. Leaf hydraulic traits such as midday leaf water potential (MWP) and leaf osmotic potential (OP) were insignificantly correlated with leaf photosynthetic physiological traits such as maximal net assimilation rate per mass (Amass). In addition, great discrepancies were found between in-situ and ex-situ measurements of photosynthetic parameters. The ex-situ measurements caused a decrease by 53.63%, 27.86%, and 38.05% in Amass, and a decrease of 50.00%, 19.21%, and 27.90% in light saturation point compared to the in-situ measurements. These findings provided insights into our understanding of the response mechanisms of P. chinensis to micro-habitat in Xishuangbanna tropical seasonal rainforests and the fine scale adaption of different resultant of decoupled traits, which have implications for understanding ecological adaption strategies of P. chinensis under environmental changes.